Pricing and Lead Time Decisions in a Duopoly Common Retailer Channel - NIU, Xiuming (Institutional Knowledge at Singapore Management University, 2010)
This thesis studies a dual-level decentralized supply chain consisting of two suppliers and two retailers facing a price- and lead-time-sensitive demand. We model the suppliers’ operations as M/M/1 queues and demand as a linear function of the retail prices and promised delivery lead-times offered to the customers. Three different kinds of games are constructed to analyze the pricing and lead-time decisions of the suppliers and retailers. We show the existence of a unique equilibrium in all games and provide the exact formulas to compute the optimal decisions for both the suppliers and retailers. We further present numerical examples to illustrate how the results of our model can be used to provide useful managerial insights for selecting the best strategies for suppliers and retailers under different market and operational environments.